A Techno-Economic Framework for Natural Gas Pipeline Tariff Determination Under State Budget Financing: Evidence from The Semarang-Batang Open-Access Transmission Pipeline, Indonesia - Aji Agraning Bawono; Sutrasno Kartohardjono (Testing Center for Oil and Gas LEMIGAS, 2026)
Natural gas pipeline tariff regulation in Indonesia has historically been designed for investor-financed infrastructure, where tariffs must recover capital costs at a commercially determined weighted average cost of capital (WACC). The Semarang-Batang Transmission Pipeline (Cisem Phase I)—the first open-access transmission pipeline in Indonesia constructed under State Budget (APBN) financing—demands a fundamentally different tariff framework. This study develops and evaluates two alternative tariff formulation models tailored to government-funded infrastructure: (i) the State Capital Participation (PMN) scheme, which recovers capital at the government's retail sukuk coupon rate (IRR = 3.97%), and (ii) the State Property (BMN) scheme, which waives capital recovery entirely and charges only a management fee (CAPEX = 0). Results show that the BMN scheme delivers the lowest tariff of USD 0.279/MSCF, representing 55.7% below the conventional WACC-based tariff (USD 0.630/MSCF) and 25.0% below the PMN scheme (USD 0.372/MSCF). Sensitivity analysis confirms the BMN scheme's structural advantage: it eliminates IRR-driven tariff volatility and maximizes affordability for industrial end-users. These findings provide a replicable techno-economic framework and a practical policy basis for BPH Migas in determining transportation tariffs for APBN-financed pipeline infrastructure across Indonesia.